2016
DOI: 10.1126/science.aaf2288
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of cancer neoantigens with donor-derived T cell receptor repertoires

Abstract: Accumulating evidence suggests that clinically efficacious cancer immunotherapies are driven by T cell reactivity against DNA mutation-derived neoantigens. However, among the large number of predicted neoantigens, only a minority is recognized by autologous patient T cells, and strategies to broaden neoantigen-specific T cell responses are therefore attractive. We found that naïve T cell repertoires of healthy blood donors provide a source of neoantigen-specific T cells, responding to 11 of 57 predicted human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
369
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(399 citation statements)
references
References 42 publications
9
369
0
1
Order By: Relevance
“…41,42 We used the peptide-MHC stability prediction tool NetMHCstabpan and could not confirm those previous reports since our results indicated that binding prediction alone performed better than both stability prediction alone and stability prediction in combination with binding.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…41,42 We used the peptide-MHC stability prediction tool NetMHCstabpan and could not confirm those previous reports since our results indicated that binding prediction alone performed better than both stability prediction alone and stability prediction in combination with binding.…”
Section: Discussionmentioning
confidence: 66%
“…41,42 To test the ability to utilize MHC-peptide stability predictions for neoepitope identification we used the prediction tool NetMHCstabpan. 43 Stability predictions alone and in combination with binding predictions, as recommended by the authors, 43 did not improve immunogenic neoepitope prediction performance when compared to binding prediction alone (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…These approaches are now being adapted to create personalized therapeutic cancer vaccines. On the other hand, it might be difficult to select immunogenic epitopes eliciting active CTLs among candidate epitopes [59,60] . It takes time to assess the immunogenicity of candidate epitopes by in vitro experiments, though the vaccine should be delivered to patients quickly.…”
Section: Neoantigens As Novel Targets Of Cancer Peptide Vaccinesmentioning
confidence: 99%
“…It was reported recently that neoantigen specific T cells that generated from healthy donors were able to recognize 11 of 57 predicted neoepitopes across three patients. This may broaden neoantigen-specific T cell reactivity, and provide a rationale for using "outsourced" T cells in curing tumor patients with dysfunctional immune system [34].…”
Section: Therapeutic Approaches Targeting Patient Specific Neoantigenmentioning
confidence: 99%